2003
DOI: 10.1063/1.1573345
|View full text |Cite
|
Sign up to set email alerts
|

High pressure behavior of titanium–silicon carbide (Ti3SiC2)

Abstract: Shock compaction and synthesis of the titanium-silicon ternary carbide ( Ti 3 SiC 2 ) AIP Conf.The dynamic high-pressure behavior and phase stability of titanium-silicon carbide (Ti 3 SiC 2 ), a unique ceramic having metal-like properties, was investigated in this study. Time-resolved measurements of the Hugoniot equation of state, employing a plate impact geometry, were conducted on the Ti 3 SiC 2 samples in the pressure range of 50-120 GPa using a two stage light gas gun. At pressures around 90-120 GPa, Ti 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…The theoretical simulation value of the bulk modulus of Ti 3 SiC 2 ceramics, predicted by using first-principle computational technique is 204 GPa [13], in agreement with the static pressure fitting value of 206 GPa [10]. Base on the previous calculations and comparison of bulk modulus of Ti 3 SiC 2 ternary ceramics estimated from various methods, Ti 3 SiC 2 shows an anomalous behavior [10]. It is very incompressible due to its similar bulk modulus (∼206 GPa) to that of TiC (∼220 GPa).…”
Section: Characterization Of Ti 3 Sicsupporting
confidence: 68%
See 2 more Smart Citations
“…The theoretical simulation value of the bulk modulus of Ti 3 SiC 2 ceramics, predicted by using first-principle computational technique is 204 GPa [13], in agreement with the static pressure fitting value of 206 GPa [10]. Base on the previous calculations and comparison of bulk modulus of Ti 3 SiC 2 ternary ceramics estimated from various methods, Ti 3 SiC 2 shows an anomalous behavior [10]. It is very incompressible due to its similar bulk modulus (∼206 GPa) to that of TiC (∼220 GPa).…”
Section: Characterization Of Ti 3 Sicsupporting
confidence: 68%
“…The measured bulk modulus of the Ti 3 SiC 2 sample used in this study, calculated from the Young's modulus (353 GPa) and Poisson's ratio (0.2) from Table 1, is 196 GPa, slightly lower than that calculated by fitting the pressure versus lattice volume data with the Birch-Murnaghan equation (206 GPa) [9,10], but about 10% higher than the values calculated from the longitudinal and transverse velocities of sound (179 GPa) [12]. The theoretical simulation value of the bulk modulus of Ti 3 SiC 2 ceramics, predicted by using first-principle computational technique is 204 GPa [13], in agreement with the static pressure fitting value of 206 GPa [10]. Base on the previous calculations and comparison of bulk modulus of Ti 3 SiC 2 ternary ceramics estimated from various methods, Ti 3 SiC 2 shows an anomalous behavior [10].…”
Section: Characterization Of Ti 3 Sicmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, a similar study indicated that -Ti 3 SiC 2 was structurally stable up to 61 GPa [32]. It has been suggested that the  phase transformation occurs at much higher pressure (~90 GPa) in Ti 3 SiC 2 [33], although it was referred to as "a more condensed state" 14 of Ti 3 SiC 2 -the  polymorph was not unambiguously identified. There are also theoretical results that suggest that this type of polymorphism may be possible for the 211 phases [34].…”
Section: Polymorphism Of Max Phasesmentioning
confidence: 93%
“…Shock waves originating from the impact of a projectile or from explosive detonation can create pressures from a few to tens of GPa, resulting in inter-particle bonding in the time duration of microseconds. [8][9][10][11] The main attraction of this approach is that fully dense bulk compacts can be fabricated without introducing significant changes in microstructure. 12) Recently, shock consolidation of bulk nanocrystalline magnetic alloys, such as NdFeB, 13) SmCo, 14) and SmFeN magnets, 15) has been reported.…”
Section: Introductionmentioning
confidence: 99%